Synthesis and applications of carbon-polymer composites and nanocomposite functional materials - Mahalingam S.; Omar A.; Manap A.; Rahim N.A. (Elsevier, 2023)
Graphene is a two-dimensional nanomaterial that has between one and ten layers of sp2-hybridized carbon atoms arranged in six-membered rings. It has impressive properties including high electron mobility, large specific surface area, high thermal conductivity, greater Youngs modulus, high fracture strength, and high optical transmittance. These properties make graphene a great potential application in energy conversion and storage devices, reinforced composites, sensors, catalysis, photonic, photovoltaic, bio-application, and biomedicines. The applications have triggered a new path in the chemical and physical modification of graphene-based materials. In this chapter, various synthesis techniques for graphene-based materials, such as mechanical/micromechanical exfoliation, electrochemical synthesis, plasma discharge etching, chemical vapor deposition, epitaxial growth on silicon carbide, and unzipping carbon nanotubes, are reviewed. Synthesis of functionalized graphene by modifying carbons bandgap and increasing graphenes specific surface area is also discussed. Hence, synthesizing graphene-based composites with precise techniques captures a flagship position in various scientific developments and technology utilizations. 2023 Elsevier Ltd. All rights reserved.